Monolayer (2D) or spheroids (3D) cell cultures for nanotoxicological studies? Comparison of cytotoxicity and cell internalization of nanoparticles - Juarez-Moreno, Karla; Chávez García, Dalia H.; Hirata, Gustavo A.; Vázquez Duhalt, Rafael (My University, 2022)
Two-dimensional (2D) cell culture monolayers are commonly used for toxicological assessments of nanomaterials. Despite their facile handling, they exhibit several constraints due to their structural and complexity differences with three-dimensional (3D) in vitro cell models, such as spheroids. Here, we conducted a comparative nanotoxicological study of fibroblasts (L929) and melanoma (B16-F10) cells, grown in 2D and 3D arrangements. The cytotoxicity, reactive oxygen species (ROS) production, genotoxicity, cell morphology complexity, and uptake of silver nanoparticles (AgNPs) and folic acid-functionalized upconversion nanoparticles (FA-UCNPs) were compared in the two culture arrangements. AgNPs cytotoxicity was higher in spheroids than in monolayer cultures. Furthermore, apoptotic cell percentages and ROS production were higher in 3D than in 2D cell cultures. More importantly, 2D cultures required twice the concentration of AgNPs than the 3D cell models to reach a considerable DNA damage index (c.a. 200). Therefore, spheroids are more sensitive to the genotoxic effects of AgNPs. FA-UCNPs exerted negligible cell toxicity in 2D and 3D cell models. Moreover, AgNPs induced disaggregation and downsizing of spheroids in a facile and concentration-dependent manner. Internalization of FA-UCNPs in spheroids was 20% higher than in the 2D cell arrangements. Collectively, our findings, demonstrated that spheroids are a more sensitive model than monolayers for the assessment of nanoparticle biocompatibility and internalization. RESUMEN Las monocapas de cultivo celular bidimensionales (2D) se utilizan comúnmente para evaluaciones toxicológicas de nanomateriales. A pesar de su fácil manejo, presentan varias limitaciones debido a sus diferencias estructurales y de complejidad con los modelos celulares in vitro tridimensionales (3D), como los esferoides. Aquí, llevamos a cabo un estudio nanotoxicológico comparativo de fibroblastos (L929) y células de melanoma (B16-F10), cultivadas en arreglos 2D y 3D. La citotoxicidad, la producción de especies reactivas de oxígeno (ROS), la genotoxicidad, la complejidad de la morfología celular y la absorción de nanopartículas de plata (AgNP) y nanopartículas de conversión ascendente funcionalizadas con ácido fólico (FA-UCNP) se compararon en los dos arreglos de cultivo. La citotoxicidad de AgNPs fue mayor en esferoides que en cultivos monocapa. Además, los porcentajes de células apoptóticas y la producción de ROS fueron mayores en cultivos celulares 3D que en 2D. Más importante aún, los cultivos 2D requerían el doble de concentración de AgNP que los modelos celulares 3D para alcanzar un índice de daño de ADN considerable (aprox. 200). Por lo tanto, los esferoides son más sensibles a los efectos genotóxicos de las AgNP. Los FA-UCNP ejercieron una toxicidad celular insignificante en modelos celulares 2D y 3D. Además, los AgNP indujeron la desagregación y la reducción del tamaño de los esferoides de una manera fácil y dependiente de la concentración. La internalización de FA-UCNP en esferoides fue un 20% mayor que en los arreglos de celdas 2D. En conjunto, nuestros hallazgos demostraron que los esferoides son un modelo más sensible que las monocapas para la evaluación de la biocompatibilidad e internalización de nanopartículas.
Toxicology in Vitro
Keywords: Spheroids; Monolayer; Nanotoxicology; Three-dimensional cell culture; Cytotoxicity; Campus Ensenada